2006
DOI: 10.1029/2006ja011806
|View full text |Cite
|
Sign up to set email alerts
|

Observations of triboelectric charging effects on Langmuir‐type probes in dusty plasma

Abstract: Investigation of Earth's mesosphere using sounding rockets equipped with a myriad of instruments has been a highly active field in the last 2 decades. This paper presents data from three separate instruments: an RF impedance probe, a DC fixed bias Langmuir probe, and an electric field probe, that were flown on a mesospheric sounding rocket flight investigating the presence of charged dust within and/or around a sporadic metal layer. The combined data set indicates a case of payload surface charging, the causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Fig. 16 The DICE LPs are deployed following launch, and extend from both ends of the sensor-sat so as to maximize wake free exposure throughout the orbit Traditionally, to acquire high resolution relative electron density measurement, an LP has been operated at a fixed-bias in the electron saturation region (Barjatya and Swenson 2006). However, at DICE spacecraft orbital speeds, the magnitude of ion ram current is significantly higher than the ion thermal current.…”
Section: Langmuir Probe (Lp)mentioning
confidence: 99%
“…Fig. 16 The DICE LPs are deployed following launch, and extend from both ends of the sensor-sat so as to maximize wake free exposure throughout the orbit Traditionally, to acquire high resolution relative electron density measurement, an LP has been operated at a fixed-bias in the electron saturation region (Barjatya and Swenson 2006). However, at DICE spacecraft orbital speeds, the magnitude of ion ram current is significantly higher than the ion thermal current.…”
Section: Langmuir Probe (Lp)mentioning
confidence: 99%
“…Among these are the nucleation of mesospheric ice particles (e.g., Rapp and Thomas, 2006), the mesospheric metal chemistry , the D-region charge balance (e.g., Rapp and Lübken, 2001), the heterogeneous formation of water vapour in the mesosphere (Summers et al, 2001), and even the nucleation of polar stratospheric cloud particles which play a major role in the formation of the ozone hole (e.g., Voigt et al, 2005). While some progress regarding the experimental investigation of these atmospheric trace species has been made over the past years with sounding rockets (e.g., Schulte and Arnold, 1992;Gelinas et al, 1998;Horányi et al, 2000;Rapp et al, 2005;Lynch et al, 2005;Barjatya and Swenson, 2006;Amyx et al, 2008;Strelnikova et al, 2009;Rapp et al, 2010), incoherent scatter radars Strelnikova et al, 2007;Fentzke et al, 2009), satellites (Hervig et al, 2009(Hervig et al, , 2012, and laboratory studies (Saunders and Plane, 2006), much of our knowledge about these particles still relies on model results (e.g., Hunten et al, 1980;Gabrielli et al, 2004;Megner et al, 2006Megner et al, , 2008Bardeen et al, 2008). Among other things, very little is still known about the physical and chemical properties of MSPs such as their composition and their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is now becoming increasingly clear that secondary charging effects, due to impacting dust particles on rocket payloads and their probes, can affect some measurements (Zadorozhny et al, 1993;Havnes et al, 1996;Vostrikov et al, 1997;Gumbel and Witt, 1998) and probably sometimes totally dominate them (Barjatya and Swenson, 2006;Havnes and Naesheim, 2007). In the last paper, it was demonstrated that secondary charging by dust particles impacting on surfaces at a high impact angle θ i (= angle with the normal to the surface), which fragmented and carried away negative charge, could give the appearance of incoming positive charges.…”
Section: Introductionmentioning
confidence: 99%